In silico evaluation of lapachol derivatives binding to the Nsp9 of SARS-CoV-2. Issue 13 (21st July 2022) - Junior, Nilson Nicolau; Santos, Igor Andrade; Meireles, Bruno Amaral; Nicolau, Mariana Sant'Anna Pereira; Lapa, Igor Rodrigues; Aguiar, Renato Santana; Jardim, Ana Carolina Gomes; José, Diego Pandeló
Abstract: SARS-CoV-2 is the etiological agent of COVID-19, which represents a global health emergency that was rapidly declared a pandemic by the World Health Organization. Currently, there is a dearth of effective targeted therapies against viruses. Natural products isolated from traditional herbal plants have had a huge impact on drug development aimed at various diseases. Lapachol is a 1, 4- naphthoquinone compound that has been demonstrated to have therapeutic effects against several diseases. SARS-CoV-2 non-structural proteins (nsps) play an important role in the viral replication cycle. Nsp9 seems to play a key role in transcription of the RNA genome of SARS-CoV-2. Virtual screening by docking and molecular dynamics suggests that lapachol derivatives can interact with Nsp9 from SARS-CoV-2. Complexes of lapachol derivatives V, VI, VIII, IX, and XI with the Nsp9 RNA binding site were subjected to molecular dynamics assays, to assess the stability of the complexes via RMSD. All complexes were stable over the course of 100 ns dynamics assays. Analyses of the hydrogen bonds in the complexes showed that lapachol derivatives VI and IX demonstrated strongest binding, with a stable or increasing number of hydrogen bonds over time. Our results demonstrate that Nsp9 from SARS-CoV-2 could be an important target in prospecting for ligands with antiviral potential. In addition, we showed that lapachol derivatives are potential ligands for SARS-CoV-2 Nsp9. Communicated by Ramaswamy H. Sarma